Effect of Merger and Acquisition on the Profitability in Nepalese Commercial Banks - Shrestha, Manoj; Kharel, Kasam; Chaudhary, Mahalaxmi; Gyawali, Mamata; Pradhan, Sumit (Nepalese Journal of Finance, 2024)
The study examines the effect of mergers and acquisitions on the profitability in Nepalese commercial banks. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are earnings per share, capital adequacy ratio, leverage, spread rate, loan-to-deposit ratio and bank size. The study is based on secondary data from 11 commercial banks with 110 observations for the study period from 2012/13 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of mergers and acquisitions on the profitability of selected Nepalese commercial banks. The study showed that earnings per share has a positive impact on return on assets and return on equity after merger and acquisition. It means that increase in earnings per share leads to increase in return on assets and return on equity. However, capital adequacy ratio has a negative effect on return on assets and return on equity after merger and acquisition. It means that decrease in capital adequacy ratio leads to decrease in return on assets and return on equity. Similarly, leverage has a negative impact on return on assets after merger and acquisition. It shows that increase in leverage leads to decrease in return on assets. Moreover, spread rate has a positive impact on return on assets and return on equity after merger and acquisition. It means that the increase in spread rate leads to increase in return on assets and return on equity. In contrast, loan to deposit ratio has as negative impact on return on assets and return on equity after merger and acquisition. It means that increase the loan-to-deposit ratio leads to decrease the return on assets and return on equity. Furthermore, bank size has a positive impact on return on equity after merger and acquisition. It shows that increase the bank size leads to increase in return on equity.